2015
DOI: 10.1002/asia.201500985
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Luminescence of Chiral Pt(pppb)Cl (pppbH=1‐pyridyl‐3‐(4,5‐pinenopyridyl)benzene) Aggregate in the Excited State

Abstract: We prepared enantiomers of chiral Pt(II) complexes, Pt(pppb)Cl and Pt(pppb)CN (pppbH=1-pyridyl-3-(4,5-pinenopyridyl)benzene), and measured their CPL (circularly polarized luminescence) spectra for excimer and trimer emission. The contribution of the pinene moiety to CPL was considerably low for the π-π* emission of the monomer but large for MMLCT (metal-metal-to-ligand charge-transfer) of the excimer and trimer which had a helical structure induced in a face-to-face stacking fashion. The trimer CPL for (+)-Pt(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 48 publications
2
37
0
Order By: Relevance
“…However, there were no such phenomenon observed for 59‐P/M and 60‐P/M . Similarly, the behavior of self‐assemblies to form stacked aggregates via Pt–Pt, π–π stacking, and dipole–dipole interactions is another effective method to enhance the dissymmetry g lum factors . For example, two novel enantiomers of Pt(II) phenylbipyridine complexes ( 61‐R/S ) with bis(phenylisoxazolyl)phenylacetylene ligands which were linked with a chiral alkyl chains were designed and synthesized .…”
Section: Phosphorescent Transition‐metal Complexesmentioning
confidence: 99%
“…However, there were no such phenomenon observed for 59‐P/M and 60‐P/M . Similarly, the behavior of self‐assemblies to form stacked aggregates via Pt–Pt, π–π stacking, and dipole–dipole interactions is another effective method to enhance the dissymmetry g lum factors . For example, two novel enantiomers of Pt(II) phenylbipyridine complexes ( 61‐R/S ) with bis(phenylisoxazolyl)phenylacetylene ligands which were linked with a chiral alkyl chains were designed and synthesized .…”
Section: Phosphorescent Transition‐metal Complexesmentioning
confidence: 99%
“…Meanwhile, the g lum values are similar to those of the reported cases for helicene derived Pt(II) complexes or square-planar Pt(II) complexes with helical structures. [10][11][12][13][14][15][16][17] Due to the short distance and interactions between the two platinum centers, the CPL bands of complex (−)-1 are dominated by the dimeric excited state 3 MMLCT. For complex (−)-2, the CPL bands mainly come from monomeric excited state 3 MLCT.…”
Section: Chiroptical Propertiesmentioning
confidence: 99%
“…4 In recent years, due to high emission quantum efficiency and tunable excited-state properties, growing attention has been paid to the development of new CPL-active materials focusing on phosphorescent transition metal complexes, such as Ir, Zn, Pt and so on. [5][6][7][8][9][10][11][12][13][14][15][16][17] Among the phosphorescent materials based on transition metal complexes, square-planar Pt(II) complexes are capable of forming self-assemblies, resulting in intriguing luminescent and conductive properties. 18,19 When a chiral substituent is incorporated, the packing of adjacent units adopts a staggered pattern alongside the Pt⋯Pt chain due to steric hindrance, which is favourable for forming a helical supramolecular structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Additionally, helical assemblies of Pt(II) complexes can be formed in solution with the introduction of optically pure groups, correspondingly leading to interesting on-off switching of chiral signals. [25][26][27][28][29][30] It is suggested that these abovementioned stimuli-induced switches can be harnessed to develop versatile sensors to detect subtle environmental changes. [31][32][33][34] 7,7,8,8-Tetracyanoquinodimethane (TCNQ) has been widely investigated as a good electron acceptor due to its high electron affinity.…”
Section: Introductionmentioning
confidence: 99%